The polysemy of the colour term white in English, Russian, Tajik and Uzbek - Zayniev Daler (ExELL (Explorations in English Language and Linguistics))
Colour is one of the central categories of both a conceptual and a linguistic world of image, correlated with an axiological and an esthetic assessment, a semiotic and value world of image of a given national culture, which allows us to talk about colour preferences, ethnic colour mentality, colour gaps and colour universals, that is, about the colour world of image. In addition, colours have senses specific to particular fields, from physics over printing to senses used in everyday life. In the present article, I carry out an analysis of the colour term white in English, and its counterparts in Russian, Tajik and Uzbek from the lexicological and lexicographical point of view, starting with a semasiological perspective, following Steinvall’s (2002: 56) methodology. The conceptual space of the colour term white in lexicographic work tends to be kept compact rather than articulated in great detail, just like in the case of other types of colours, i.e. in an attempt to minimize polysemy, its senses are typically lumped, rather than split. The main aims were to investigate the differences in the representation of adjectives denoting white colour across languages and to compare monolingual and bilingual dictionaries with respect how they structure their meanings, as well as collocations and idiomatic expressions (often based on metaphors and metonymies). A number of field-like clusters of concepts related to the colour terms for white were established. Based on these findings, I proceed to make some suggestions for the improvement of the approach to colour terms for white and other colours in general use and pedagogical dictionaries.